The Effect of CEO Competence on Earnings Management: The Role of CEO Reputation - Faisal, Muhammad; Hermawan, Ancella A (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to obtain empirical evidence related to the effect of CEO competence on earnings management and the role of CEO reputation in moderating the influence of CEO competence on earnings management. Three types of earnings management are used in this study, which are aggregate, accrual, and real earnings management. The sample used is non-financial companies listed on the Indonesia Stock Exchange in 2015-2017. The results of testing on the CEO competency show that the influence of CEO competency in pressing earnings management only occurs in aggregate and accrual earnings management, while the CEO competency in pressing real earnings management has no influence. In addition, the results of this study indicate that the role of CEO reputation consistently strengthens the influence of CEO competency in pressing aggregate earnings management, but the role of CEO reputation tends to have a substitution role, which is to weaken the influence of CEO competency on accrual earnings management. Meanwhile, the role of the CEO’s reputation does not show an influence on real earnings management activities.